Tree-cavity formation in the mature subtropical forests of Yambaru, Okinawa Island. Issue 6 (2nd November 2021) - Takashima, Atsushi; Nakanishi, Akira; Morishita, Mina; Abe, Shin; Saito, Kazuhiko; Kotaka, Nobuhiko
ABSTRACT: Tree-cavities are considered as key components that support multiple species, including endemic ones, in subtropical forests in Yambaru, the northern area of Okinawa Island, Japan. Here, we established two study plots in mature subtropical forests in Yambaru and surveyed for tree-cavities with depths ≥ 10 cm. The density of tree-cavities was 198 per ha, which is exceptionally high compared with tree-cavity densities reported by other studies. Among the three key tree species ( Castanopsis sieboldii, Schima wallichii, and Distylium racemosum ), no tree-cavities were observed in S. wallichii in the study plots. In both C. sieboldii and D. racemosum, the probability of tree-cavity presence increased as the diameter at breast height (DBH) increased. In addition, the probability of tree-cavity presence on D. racemosum started to increase at smaller DBH stage compared with that on C. sieboldii. Distylium racemosum often had multiple tree-cavities per stem. Excavated cavities were rare across all species, and decay cavities were dominant. We detected the activity of the endangered Ryukyu long-haired rat ( Diplothrix legata ) in two cavities, both of which had similar features: a stem DBH of about 43 cm and volumes of 0.09–0.16 m 3 . In the Yambaru area, the preservation of large-diameter stems that will form tree-cavities is critically important for maintaining forest ecosystem health and should be considered when implementing forest management plans, especially for D. racemosum, which is rich in cavities and likely plays multiple ecological roles.